The evolution of the palate in South African Anomodontia and its classificatory significance - Toerien, M.J . (Bernard Price Institute for Palaeontological Research, 1953)
In this work an attempt is made to find a basis for the classification of the South African Anomodontia, unaffected by sex and age variations. The structure of the palate provided such a basis. The evolution of the palate was followed from the early Endothiodonts, through the genus Dicynodon and other forms formerly referred to this genus, to the more advanced Anomodonts. Of the Endothiodonts the genera Brachyprosopus, Emydopsis and Diaelurodon are transferred to Brachyuraniscus, Emydops and Pristerodon respectively. Three new genera, Broilius, Hueneus and Parringtoniella are described, as well as three new species to existing genera (Emydops kitchingi, Emydops murraysburgensis and Pristerodon buffaloensis). Owen's genus Oudenodon and van Hoepen's genus Daptocephalus are reintroduced and three new species of Dicynodon are described (D. vanderhorsti, D. antjiesfonteinensis and D. schroderi). The evolution of the palate. is followed further to the genera Cistecephalus, Aulacocephalodon, Platycyclops, Kitchingia, Pelanomodon, Lystrosaurus and Kannemeyeria.
Keywords: Anomodontia, South African, palate